A novel miniaturized radiometer front-end for early breast cancer detection using ultra-wideband flexible antenna - Elouerghi, Achraf; Khomsi, Zakaryae; Bellarbi, Larbi; Jbari, Atman (Institute of Advanced Engineering and Science, 2024)
This article introduces a new design of the front-end part of a passive and miniature radiometer, which has been developed to detect breast cancer at an early stage, by measuring temperature in deep mammary tissues. The design and simulation of each element of the microwave radiometer are carried out using computer simulation technology microwave (CST MWS) software. The proposed measurement system consists of a miniaturized ultra-wideband (UWB) flexible antenna operating in the S-band (2-4 GHz), a breast phantom, a low noise amplifier (LNA), a bandpass filter, and a radio frequency (RF) power detector. These components were combined with active circuits to build the front-end system using the co-simulation modules provided by the CST MWS. The method is based on the concept that the virtually created tumor increases the temperature inside the breast phantom, and to detect the abnormality, we applied the proposed radiometer front-end on breast phantom to measure the gain variation. The results demonstrated that the design of the proposed miniaturized radiometer has promising performance in terms of stability and gain variation, indeed, the difference in maximum gain |ΔGmax| measured between abnormal and healthy phantom is about 0.92 dB at 2.75 GHz. This indicates its potential for detecting breast tumors.